Pornography and sexual offense committed by adolescents in Brazil:: a narrative review - Almeida de Espindola, Bárbara (2023)
This narrative review aims to expand the contribution on the association between pornography consumption and sexual offenses committed by adolescents. After reviewing previous published researches on the subject, the discussion was organized into three topics: (1) socioeconomic and family conditions; (2) encouragement of early sexual initiation; (3) encouragement of violence and sexual violence in particular. The theoretical framework of the new-paradigmatic systemic thinking was used to discuss the articles in the method, since this association demands a different conception of the traditional thinking of causality, due to the complexity of the interactions of the contextual elements. The majority of scientific production on the subject was found in international studies, pointing out the necessity for further studies in the Brazilian context. It was concluded that the association between pornography consumption and sexual offense by adolescents occurs from the interaction between certain characteristics of the actors in the context and vulnerability factors.